Eficiência reprodutiva de matrizes de frango de corte suplementadas com cantaxantina - Lucca, Érica Crosara Ladir de (2017)
The supply of chicken meat in Brazil has accompanied the growth of domestic and foreign demand to attend the increased competitiveness and productivity. In order to serve the markets, genetics companies have been working to improve the zootechnical indexes of the sector, such as fertility and hatching of the broilers breeders. In this context, it is essential to meet excellent standards of fertility and hatching. Free radicals, present in the productive and reproductive process can cause damage through the oxidation of lipids and DNA alterations, causing dysfunction and cell death. The inclusion of substances with antioxidant properties in the diet assists the enzyme defense system in controlling the damage caused by free radicals in cells, such as the spermatozoa of the male. Carotenoids are an example of this type of substance because they have antioxidant, pigmentary, provitamin and immunomodulatory activities. Canthaxanthin is a member of the carotenoid group and it is an important antioxidant because it removes free radicals, absorbs and dissipates excess energy, and recycles vitamin E. Studies have shown that this additive can help to effectively reduce lipid peroxidation in various tissues and In embryos of birds, also improving the fertility index in lots of broiler chicken matrices in old age. The objective of this research was to study the action of canthaxanthin on the reproductive efficiency of broiler breeders. The rates of hatching, fertility, number of sperm perforations in the peri-egg membrane of the eggs, testicular development through measurements of the seminiferous tubules, and the chromatin compaction of the spermatozoa of the male were evaluated. The research was carried out in a conventional house for the production of heavy bredeers, where the experimental feeds were offered from the 22nd week of life. For the experiment, the following treatments were used: Treatment 1 - 10,500 females and 1,500 males, housed in a shed with canthaxanthin supplementation; Treatment 2 - 10,500 females and 1,500 males, housed in a shed without 6 ppm of canthaxanthin in the diet from 22 weeks of age. Hatching rates and sperm perforation rate in peri-egg membrane were analyzed at weeks 30, 40 and 50, at weeks 30 and 50 the degree of sperm chromatin compaction was analyzed, at 40 weeks the testicular development of males , And fertility after 50 weeks of batch life. Differences were found between the number of sperm perforations at 30, 40 and 50 weeks of age, and at the three ages observed, the highest sperm perforation rate occurred in the batch supplemented with canthaxanthin. In this study, we also observed better hatch rates at the age of 35 to 45 weeks of bird life, and a higher fertility rate after 50 weeks of life, during which fertility analysis was possible to be performed in the field. Regarding the life time analyzed, the behavior of the mean perforations in the peri-egg membrane of the eggs was similar, presenting a proportional drop in the last week tested. The results of chromatin compaction of spermatozoa indicated a higher degree of partial or total decompression of roosters not supplemented with canthaxanthin. When analyzed for age, antioxidant treatment in the diet showed smaller changes in chromatin compaction at 50 weeks of age compared to week 30. This suggests that the addition of the antioxidant was important in protecting the effects of age on the Patterns of reproductive efficiency. At week 30 of rooster life, the probability of observing changes in sperm chromatin compaction of roosters not supplemented with canthaxanthin is 1.82 times higher than in supplemented roosters at week 50, this probability increases to 5, 78 times, in this case, the greater the chance of observing changes in the chromatin compaction of the spermatozoa of roosters that did not receive the antioxidant in the diet. It was concluded that the use of canthaxanthin as an antioxidant in the diet can minimize the deleterious effects of free radicals on spermatozoa, including changes in sperm chromatin.